2012
DOI: 10.1007/s10021-011-9516-9
|View full text |Cite
|
Sign up to set email alerts
|

Variable Responses of Lowland Tropical Forest Nutrient Status to Fertilization and Litter Manipulation

Abstract: Predicting future impacts of anthropogenic change on tropical forests requires a clear understanding of nutrient constraints on productivity. We compared experimental fertilization and litter manipulation treatments in an old-growth lowland tropical forest to distinguish between the effects of inorganic nutrient amendments and changes in nutrient cycling via litterfall. We measured the changes in soil and litter nutrient pools, litterfall, and fine root biomass in plots fertilized with nitrogen (N), phosphorus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
76
4
6

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(99 citation statements)
references
References 76 publications
8
76
4
6
Order By: Relevance
“…"Available" nutrients, including KCl-extractable ammonium (NH 4 ) and nitrate (NO 3 ) and Mehlich-III extractable P, potassium (K), calcium (Ca), magnesium (Mg) and micronutrients, all changed over 4 years in the upper 2 cm of soil as a result of litter manipulation . After 6 years of litter manipulation, surface soils (0-10 cm) had lower NO 3 and K in litter removal plots and higher NO 3 and Zn in litter addition plots; other nutrients were not significantly affected (Sayer et al, 2012). In Costa Rica after 2.5 years of litter manipulation, surface soils (0-10 cm) had lower net nitrification in both litter removal and addition treatments, while NH 4 concentrations were significantly lower in litter removal plots (NH 4 was 83-91 % of the extractable N; Wieder et al, 2013).…”
Section: Introductionmentioning
confidence: 91%
“…"Available" nutrients, including KCl-extractable ammonium (NH 4 ) and nitrate (NO 3 ) and Mehlich-III extractable P, potassium (K), calcium (Ca), magnesium (Mg) and micronutrients, all changed over 4 years in the upper 2 cm of soil as a result of litter manipulation . After 6 years of litter manipulation, surface soils (0-10 cm) had lower NO 3 and K in litter removal plots and higher NO 3 and Zn in litter addition plots; other nutrients were not significantly affected (Sayer et al, 2012). In Costa Rica after 2.5 years of litter manipulation, surface soils (0-10 cm) had lower net nitrification in both litter removal and addition treatments, while NH 4 concentrations were significantly lower in litter removal plots (NH 4 was 83-91 % of the extractable N; Wieder et al, 2013).…”
Section: Introductionmentioning
confidence: 91%
“…Previous studies in the Gigante experiment have reported treatment effects on litter N and P (Kaspari et al 2008;Sayer et al 2012;Mayor et al 2014) but have not examined seasonal variation.…”
Section: Seasonal Dynamics Of Soil Organic Mattermentioning
confidence: 99%
“…For example, P addition to a lowland forest in Costa Rica increased soil respiration at rates expected to manifest in a long-term decrease in soil C content . On the other hand, N addition is predicted to increase soil organic C by increasing forest productivity (Sayer et al 2012) and reducing priming effects through a decline in the microbial demand for N from soil organic matter (Nottingham et al 2012). Indeed, the addition of N for several years to tropical forests in Puerto Rico increased soil organic C stocks, primarily in the mineral-associated pool (Cusack et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Si bien varios estudios han reportado variación en la PPN hojarasca con la disponibilidad de nutrientes (Vitousek 1984, Aragão et al 2009), ello es detectable solamente cuando existe un verdadero gradiente de fertilidad generado con la comparación de bosques tropicales con diferente concentración de nutrientes (Silver 1994), como lo reportaron Aragão et al (2009), quienes para evaluar la relación entre la PPN y el suelo en la Amazonia utilizaron un rango de disponibilidad edáfica de P de entre 7,3-80,0 ppm. Asimismo, el gradiente de fertilidad se puede inducir experimentalmente mediante la aplicación de nutrientes y fertilizantes al suelo (Mirmanto et al 1999;Kaspari et al 2008;Sayer et al 2012), lo cual no se hizo en el presente estudio. Segundo, la magnitud y patrones espaciales de PPN hojarasca en ecosistemas boscosos están determinados por factores biológicos tales como especie arbórea, tasas de crecimiento, edad, área basal, densidad y particulares del dosel (Bray y Gorham 1964).…”
Section: Parámetrosunclassified